Kualitas Minyak Ikan Lele Dumbo (Clarias gariepinus) Selama Penyimpanan dengan Penambahan Likopen Kasar dari Buah Tomat: Quality of Dumbo Catfish Oil (Clarias gariepinus) During Storage with The Additing of Crude Lycopene from Tomatoes - Heince Andre Pua; Nurhaeni; Erwin Abdul Rahim; Prismawiryanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
The quality of Dumbo Catfish (Clarias gariepinus) oil can be maintained during storage with the addition of crude lycopene in tomatoes as an antioxidant. The purpose of this study was to obtain the best ratio between crude lycopene in tomatoes and Dumbo catfish oil during storage. The study was conducted using a variable ratio of crude lycopene: Dumbo catfish oil with 4 treatment levels (6:40, 8:40, 10:40, and 12:40 (w/v)) and storage time variables of 1, 2, 3, and 4 weeks. Lycopene levels in Dumbo catfish oil were analyzed using a UV-Vis spectrophotometer, while the quality of Dumbo catfish oil during storage was determined through peroxide value analysis. The results showed that the best ratio of crude lycopene of tomatoes: Dumbo catfish oil was 12:40 at the third week of storage with lycopene content of 0.257 grams and the peroxide value of Dumbo catfish oil was 3.45 meq/kg or had met IFOS standards. Keywords: Crude lycopene, tomato fruit, dumbo catfish oil, peroxide value.